Determinants of COVID-19 Vaccine Uptake in Adolescents 12–17 Years Old: Examining Pediatric Vaccine Hesitancy Among Racially Diverse Parents in the United States - Gray, Aaliyah; Fisher, Celia B. (Frontiers in Public Health, 2022)
As of December 8, 2021, 9.9 million U.S. adolescents ages 12–17 years old remain unvaccinated against COVID-19 (SARS-CoV-2) despite FDA emergency approval of the Pfizer-BioNTech COVID-19 vaccine for use among this age group in May 2021. A slow-down in adolescent vaccine uptake and increased likelihood of hospitalization among unvaccinated youth highlight the importance of understanding parental hesitancy in vaccinating their adolescent children against COVID-19. Racial/ethnic disparities in pediatric COVID-19 infection and hospitalization further underscore the need to examine parental vaccine acceptance and hesitancy among diverse U.S. parent populations. In October 2021, 242 Hispanic and non-Hispanic Asian, Black, and White parents of adolescents ages 12–17 years participated in a national online survey assessing determinants of COVID-19 pediatric vaccine hesitancy. Compared to Asian, Black, and Hispanic parents, non-Hispanic White parents reported reduced odds of having vaccinated their adolescent. Bivariate analyses and a multivariable binomial logistic regression indicated that identification as non-Hispanic White, parental COVID-19 vaccine status and safety measures, COVID-19 misconceptions, general vaccine mistrust and COVID-19 related collectivist and individualist attitudes accounted for 45.5% of the variance in the vaccine status of their adolescent children. Our findings draw attention to the urgent need to consider the COVID-19 beliefs, attitudes, and behaviors of parents from diverse racial/ethnic groups in developing population tailored public health messaging to increase adolescent COVID-19 vaccine uptake.